Bank digital transformation, bank competitiveness and systemic risk - Jia, Kaiwei; Liu, Xinbei (Frontiers in Physics, 2024)
The aim of this paper is to analyze the impact of the digital transformation of banks on their systemic risks.We find that the digital transformation of commercial banks can significantly inhibit the systemic risk of banks, and this conclusion is still valid after considering the endogeneity of the model. The bank's digital transformation reduces its systemic risk by increasing its own competitiveness. Further analysis shows that the reduction of banks' marginal costs due to digital transformation is a key factor in promoting banks' competitiveness as the mechanism by which digital transformation reduces banks' systemic risk. The role of bank digital transformation in reducing systemic risk is heterogeneous, which is more obvious in large commercial banks, commercial banks that have not established financial technology subsidiaries, and systemically important banks.